The Ethics of Advising on Regulatory Compliance: Autonomy or Interdependence? - Parker, Christine (Journal of business ethics, 2000)
Many companies are now implementing ethics and regulatory compliance programs. The growth of employment of both lawyers and specialist "compliance professionals" to advise on and facilitate implementation of these programs has expanded concomitantly. This paper examines the ethical role that should be played by these advisors. Traditional ways of conceptualising corporate lawyers' ethics are shown to be inadequate because they see the legal advisor as an autonomous adversarial advocate or an independent and aloof counsellor. Instead interviews with compliance practitioners are used to show that a superior conceptualisation of the compliance advisor's role is emerging. Compliance practitioners identify explicitly with business and, at the same time, identify with a broader ethical community of other compliance professionals, regulators and stakeholders in order to play a transformative role within the organisation. This conception recognises the interdependence between compliance advisor and corporate client.